2012
DOI: 10.1111/j.1440-6055.2011.00855.x
|View full text |Cite
|
Sign up to set email alerts
|

Beetle communities associated with the tree fernDicksonia antarcticaLabill. in Tasmania

Abstract: Tree ferns are a conspicuous element of many wet forests in Australia, and in increasing demand in export markets, but little is known about their beetle fauna. The tree fern Dicksonia antarctica Labill. was sampled over four seasons at four sites in Tasmania. A total of 108 species of beetles, representing 35 families, were collected from three discrete microhabitats on 80 individual tree ferns. Beetle numbers were highest in the crown litter, then live fronds and least from the trunk. Curculionoids were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Tree ferns -Understorey tree ferns (Order Polypodiales) have a single erect trunk and very large fronds, making them important microhabitats for amphibians, mites, spiders and several arthropods including beetles (Shuter and Westoby 1992;Richards 2007;Li, Wang et al 2011;Fountain-Jones, McQuillan et al 2012). We measured height and diameter at breast height (dbh) of all ferns >5 cm dbh (following (Gilroy, Woodcock et al 2014).…”
Section: Live Vegetationmentioning
confidence: 99%
“…Tree ferns -Understorey tree ferns (Order Polypodiales) have a single erect trunk and very large fronds, making them important microhabitats for amphibians, mites, spiders and several arthropods including beetles (Shuter and Westoby 1992;Richards 2007;Li, Wang et al 2011;Fountain-Jones, McQuillan et al 2012). We measured height and diameter at breast height (dbh) of all ferns >5 cm dbh (following (Gilroy, Woodcock et al 2014).…”
Section: Live Vegetationmentioning
confidence: 99%
“…2006; Bowkett 2011; Fountain‐Jones et al . 2012); and anthropogenic and natural disturbance (e.g. Ough & Murphy 2004; Turner et al .…”
Section: Methodsmentioning
confidence: 99%
“…2006; Fountain‐Jones et al . 2012). Like the majority of the rainforest species, tree ferns are shade tolerant when establishing in the understory of the mature forest but take advantage of gaps in the canopy from tree falls, wind damage and lightning strikes to increase their height and range (ABARES 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers hypothesise that fern-feeding insects should have fewer species, genera and families than those of seed plants ( Weintraub et al 1995 ), while others suggest that the richness of fern-feeding insects is largely underestimated ( Auerbach and Hendrix 1980 , Mehltreter et al 2010 ). The possible underestimation might be deduced from the following facts: (1) many fewer investigations have been performed for wild ferns than for cultivated ferns or invasive ferns ( Fountain-Jones et al 2012 ); (2) many more fern herbivores have been discovered in the comprehensive screening of bio-control agents for pest ferns ( Mehltreter et al 2010 ); (3) no noticeable difference has been found between leaf herbivory loss of ferns and that of seed plants ( Chandra and Srivastava 2003 ); and (4) the possible biases of plant apparency (i.e. body size, distribution range and individual numbers ( Dai et al 2017 )) are not considered for phytophagous insects on ferns in comparison to those on seed plants ( Auerbach and Hendrix 1980 ).…”
Section: Introductionmentioning
confidence: 99%